Carrier engineering of Zr-doped Ta3N5 film as an efficient photoanode for solar water splitting. Issue 11 (17th May 2021) - Zou, Xin; Han, Xueyang; Wang, Chengxiong; Zhao, Yunkun; Du, Chun; Shan, Bin
Abstract : Ta3 N5 is regarded as a promising candidate material with adequate visible light absorption and band structure for photoelectrochemical water splitting. Abstract : Ta3 N5 is regarded as a promising candidate material with adequate visible light absorption and band structure for photoelectrochemical water splitting. However, the performance of Ta3 N5 is severely limited by the surface recombination as well as the mismatch between the hole diffusion length and light absorption depth. We report here a facile method to prepare a high-efficiency Ta3 N5 planar photoelectrode with Zr doping. When doped with Zr, the measured photocurrent density of the Ta3 N5 photoanode increased from 5.4 mA cm −2 to 7.2 mA cm −2 at 1.23 VRHE with Co(OH) x catalyst decoration, while the onset potential shifted negatively by 120 mV. Through electrochemical tests and structural characterization, it was found that Zr doping increased the surface oxygen concentration and reduced the interfacial charge transport resistance. Doping was also beneficial for surface passivation and the suppression of electron–hole recombination. As a result, the photogenerated voltage of Ta3 N5 increased with simultaneous Zr doping and catalyst decoration, which was conducive to the charge separation and transfer behaviour.